Psychological Capital, Social Support, and Career Capital of Indonesian Students in Taiwan - Su Jo Ching; Ibnu Siswanto; Rina Febriana (Jurnal Pendidikan Teknologi dan Kejuruan, 2019)
International experience helps people to obtain an excellent human capital which significantly plays a crucial role to predict individuals’ accomplishment both in academic and career. Therefore, this study purports to explore the psychological capital, social support, and career capital among Indonesian students who study in Taiwan. The participants consist of 120 students who were randomly selected and completed the online questionnaires. The findings of this study revealed that Indonesian students who study in Taiwan achieve an above average on their career capital, social support, and psychological capital. Furthermore, there were high and medium relationships among the three variables. It also demonstrated that students’ social support fully mediated the relationship between students’ career capital and psychological capital. Based on the research findings, conclusions and practical implications were provided.